Internet freedom and social media effects: democracy and citizen attitudes in Latin America. Issue 5 (12th September 2016) - Gainous, Jason; Wagner, Kevin; Gray, Tricia
Abstract : Purpose: The purpose of this paper is to theorize the heightened exposure to information via the internet can lead citizens to be more critical about political conditions in their countries because using social media increases the likelihood of being exposed to dissident information. Further, the authors argue that the degree to which information is restricted, or internet access is limited, across countries can decrease this effect simply because the likelihood of exposure to a dissident flow is diminished. Design/methodology/approach: The authors used survey data from the 2010 Latino Barometer to estimate a series of multilevel models to test whether citizens' attitudes about the political conditions and about democracy in their respective countries worsen, and whether this effect is stronger in countries with higher internet freedom. Findings: The results confirm that social media use has a negative influence on citizens' attitudes about their national political conditions. In addition, respondents from those countries with more internet freedom tended to have more positive attitudes about their democracy and political conditions, generally. However, as a result of more internet freedom, the negative effects of internet and social media use on these attitudes was more pronounced in countries with more internet freedom. Originality/value: These results suggest that the flow of information via the internet has substantial effect on how people feel about their government. This could be consequential for political stability, particularly in countries the conditions are not favorable. That said, these results also suggest that governments can actively decrease the odds of this dissidence building by controlling the flow of information.